Etiological Factors in Patients with Lower Gastrointestinal Bleeding at a Tertiary Care Hospital of Islamabad Pakistan: Etiological Factors in Patients with Lower Gastrointestinal Bleeding - Zada, Ikram; Ahmed, Nazeer; Tabassum, Rukhsana; Naqvi, Mehdi; Dar, Savida Ilyas; Abdullah, Muhammad (Pakistan Journal of Health Sciences, 2025)
Lower gastrointestinal bleeding (LGIB) is a significant contributor to morbidity and mortality worldwide. Its etiology varies based on age, comorbid conditions, and individual risk factors. Objectives: To identify the etiological factors associated with LGIB in patients treated at a tertiary care hospital in Islamabad, Pakistan. Methods: A retrospective analytical study was conducted on 250 patients diagnosed with LGIB at the Gastroenterology Department of Federal Government Polyclinic Hospital, Islamabad. The data included patients seen in the Outpatient Department and the Emergency Department. Data were collected from hospital records, including sociodemographic details, clinical presentations, Colonoscopy and endoscopic findings. Statistical analysis was performed using SPSS version 26.0, employing descriptive statistics and chi-square tests to evaluate associations between etiological factors and bleeding severity. Results: Patients with LGIB universally presented with PR bleeding (250; 100%) and a high rate of anemia (170; 68%). Constipation (132; 52.8%) and abdominal pain (82; 32.8%) were common, while weight loss (59; 23.6%), diarrhea (27; 10.8%), and melena (24; 9.6%) were less frequent. Older patients (>50 years) showed higher rates of rectal polyps (22; 27.5%), rectal masses (18; 22.5%), and colonic masses (14; 17.5%). Admitted patients had more rectal masses (16; 20.0%) and colonic masses (12; 15.0%) than outpatients, highlighting the severity of disease in hospitalized cases. Conclusions: The study revealed hemorrhoids as the most frequent cause of lower gastrointestinal bleeding, followed by rectal ulcers, colitis, and rectal masses. Diverticulosis was notably uncommon in this population.